Devising a method for receiving a multidimensional signal using high-order phase difference modulation in next-generation mobile networks - Halahan, Nataliia; Berkman, Liubov; Drobyk, Oleksandr; Makarenko, Anatoliy; Zavatskyi, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of receiving multidimensional signals formed on the basis of high-order phase-difference modulation of the data transmission system. The development of mobile networks of the next generations is accompanied by increased requirements for the speed, reliability, and noise immunity of information transmission. Existing modulation methods provide an increase in the speed of information transmission by reducing noise immunity and increasing the spectral width of the signal. The general unsolved problem is the lack of an effective method for forming a multidimensional signal of the nth multiplicity and receiving it based on high-order phase-difference modulation, capable of improving the efficiency of these parameters. The work proposes a method that makes it possible to form a three-dimensional multi-position signal 3D AFM-32, which uses three independent parameters – amplitude, phase, and time. A feature of the result is that noise immunity is ensured without increasing the spectral width of the signal, but due to three-dimensional formatting, which increases the distance between signal points by 50%. A coherent reception algorithm has been developed that provides accurate signal recovery even in the presence of phase or frequency disturbances. It is shown that the reception efficiency is achieved at an averaging interval of not less than M = 20, at which the system demonstrates an error probability at the level of SER≈10⁻8 at Eb/N0 ≈ 17.4 dB. This makes it possible to obtain an energy gain of 2–3 dB compared to QAM-32 and classical AFM. The proposed approach is invariant to phase shifts due to the first and second order phase differences, which eliminates ambiguities during reception. 3D AFM-32 demonstrated higher noise immunity compared to QAM-16/32 and AFM-16/32 under the same conditions. The results could be used in 5G/6G networks, in particular in adaptive OFDM systems, autonomous transport, and telemetry